Soil Microbiology Unit - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2022)
Moses, a consultant, takes students on a tour around the soil microbiology unit of IITA where biological means are used in fixing nitrogen into the soil. Some equipment found in the laboratory are: Flow hood(sterile environment): where rhizobia are being cultured Incubator for preserving and growing Rhizobia Deep freezer for preserving and retarding the growth of rhizobia Microscope for studying the roots of mycorrhiza. Etc